Causes and management of blunt liver trauma in a tertiary care hospital in Peshawar: Blunt Liver Trauma - Khan, Asad Ullah; Ahmad, Kamran; Jehanzeb Khan, Abeer; Bakhtiar, Nasir; Arsalan Tahir, Ahmad; Harris, Muhammad; Jehangir Khan, Muhammad; Haris, Sobia; Deeba, Farah (Pakistan Journal of Health Sciences, 2022)
Trauma is the principal reason of deaths in kids and young adults globally. Objective: To determine the causes and management of blunt liver trauma in a tertiary care hospital in Peshawar. Methods: The present investigation observed a total of 150 individuals through non-probability consecutive sampling to determine the mean hospital stay in patients presented with blunt liver trauma. Results: In this study, age distribution among 150 patients was analyzed as n= 10-20 Years 51 34.0%), 21-30 Years 35 (23.3%), 31-40 Years 16 (10.7%), 41-50 Years 23 (15.3%), 51-60 Years 25 (16.7%). Mean age was 41.56±5.357 years. Gender wise Distribution among 150 Patients was analyzed as Male were 94 (62.7%) and female were 56 (37.3%) Distribution of BMI among 150 patients were analyzed as n=Below 18.5 Underweight 76 (50.7%), 18.5–24.9 Normal weight 35 (23.3%), 25.0–29.9 pre-obesity 21 (14.0%), 30.0–34.9 Obesity class 18 (12.0%). Distribution Mechanism of Injury among 150 patients were analyzed as n= RTA was 57 (38.0%), fall from height was 52 (34.7%), Sport's injury was 18 (12.0%), physical assault was 23 (15.3%). Successful Conservative Management among 150 patients were analyzed as n= Yes was 106 (70.7%) and No was 44 (29.3%), Distribution of Mortality among 150 patients were analyzed as n= Yes was found 66 (44.0%) and No was found 84 (56.0%). Conclusions: The severity of liver damage and concomitant intra-abdominal injuries demonstrated a strong association with the chance of success with conservative therapy. The restricted hospital facilities and lack of agreement on traditional therapy had a detrimental influence on success.